Composite materials combining multiple luminescent MOFs and superparamagnetic microparticles for ratiometric water detection - Wehner, T.; Seuffert, M. T.; Sorg, J. R.; Schneider, M.; Mandel, Karl; Sextl, G.; Mueller-Buschbaum, K. (Journal of Materials Chemistry C, 2017)
Smart optical composite materials suitable for ratiometric sensing applications and harvesting options have been developed. The hybrid materials consist of core/shell particles with Fe3O4/SiO2 as the core and different luminescent lanthanide-containing metal-organic frameworks (MOFs) as the shell. The magnetic properties enable collection of microparticles via an external magnetic field and, thus, a strong signal augmentation of the luminescence signal. Thereby, MOF luminescence functions as a read-out signal of the sensing that can be influenced by different chemical compounds, e.g. by quenching with low concentrations of water. The combination of MOFs, which contain different luminescence centers combined with a different sensitivity towards water, results in a system that can be exploited as a ratiometric sensor. We have utilized the MOFs 3∞[Eu2(BDC)3]·2H2O·2DMF (BDC2- = benzene dicarboxylate) and 2∞[Ln2Cl6(bipy)3]·2bipy (Ln = Eu, Tb; bipy = 4,4′-bipyridine) for functionalization of the microparticles, resulting in a color-tuned yellow-emitting mixed-MOF composite system together with a Fe3O4/SiO2 core. Interaction with water decreases the luminescence unequally for both luminescence centers, which enables a quantitative determination of the water content by analysis of the ratio of the Tb3+ and Eu3+ luminescence bands. This process is supported by possible harvesting via superparamagnetism of the composite. Altogether, high sensitivity with a detection limit of 0.3% (20 μg) is achieved, equal to Karl-Fischer titration but also suitable for an "on-the-fly" analysis.
CRIS-Team Scopus Importer:2020-04-02